2019
DOI: 10.1111/eth.12841
|View full text |Cite
|
Sign up to set email alerts
|

Male chemical cues as reliable indicators of infection in the wolf spider Schizocosa ocreata

Abstract: Sexual signals can convey important information about mate quality, such as critical information about a signaler's health status, helping an individual to avoid infected or immunocompromised conspecifics. Chemical signals are especially important in this context, because they represent an honest and dynamic signaling modality that receivers can use to make updated mate choice decisions to avoid compromising their own health. In this study, we investigated the viability of male chemical cues in the wolf spider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Here, immune challenge neither affected male pheromone signals, nor their attractiveness to females. In the only previous study investigating a correlation of chemical cues and immune function in spiders, on the other hand, video playbacks of a courting male wolf spider, Schizocosa ocreata , of average size and vigour were less attractive to females when presented together with filter paper containing chemical cues of males that were experimentally infected as compared with untreated males (Gilbert & Uetz, 2019). Likewise, recent studies on female pheromones in moths revealed contradicting results on relationships between immune system function and pheromone signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, immune challenge neither affected male pheromone signals, nor their attractiveness to females. In the only previous study investigating a correlation of chemical cues and immune function in spiders, on the other hand, video playbacks of a courting male wolf spider, Schizocosa ocreata , of average size and vigour were less attractive to females when presented together with filter paper containing chemical cues of males that were experimentally infected as compared with untreated males (Gilbert & Uetz, 2019). Likewise, recent studies on female pheromones in moths revealed contradicting results on relationships between immune system function and pheromone signals.…”
Section: Discussionmentioning
confidence: 99%
“…However, only few studies investigate a link between body condition and chemical traits in spiders. Gilbert and Uetz(2019) found that females of the wolf spider Schizocosa ocreata can discriminate between experimentally infected and control males based on cuticular cues. Moreover, an elegant study on the evolutionary background of male mate preferences in tow species of widow spiders (Johnson et al, 2011; MacLeod & Andrade, 2014), Baruffaldi and Andrade (2015) showed that males can discriminate fed from starved females by silk extracts alone.…”
Section: Introductionmentioning
confidence: 99%
“…Future physiological and microbiome research is needed to understand how the modification of bacterial communities in and on the body can alter behaviour. In S. ocreata , like in A. pennsylvanica , sexual partners also appear to be able to detect the presence of bacteria (pathogenic or otherwise) in their prospective sexual partners (Gilbert, Karp, & Uetz, ; Gilbert & Uetz, , ). We found no evidence that treatment with antibiotics altered courtship behaviour or survivorship, though future studies could ascertain whether antibiotic treatments reduced the presence of beneficial microbes that might play a role in spider mating.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, females might not show a high TF response to some chemical cues because this information would not be useful in the social context of our behavioral experiment. Thus, for example, in the wolf spider ( Schizocosa ocreat ), females did not show the ability to discriminate between male and female chemical signals and a blank control in a scent choice test, but another experiment suggests that females can use the chemical information in the context of males’ infection (Gilbert & Uetz, ). In a behavioral experiment with Podarcis muralis lizards, females did not choose between male morphs based on color or chemical cues, but they were more active when presented only to males’ scents (Sacchi et al, ).…”
Section: Discussionmentioning
confidence: 99%